Effects of three different types of exercise on blood leukocyte count during and following exercise - Natale, Valéria Maria; Brenner, Ingrid K.; Moldoveanu, Andrei Ion; Vasiliou, Paris; Shek, Pang; Shephard, Roy Jesse (São Paulo Medical Journal, 2003)
CONTEXT: High-intensity exercise causes tissue damage, production of stress hormones, and alterations in the function and quantity of various immune cells. Many clinical-physical stressors such as surgery, trauma, burns and sepsis induce a pattern of hormonal and immunological response similar to that of exercise. It has thus been suggested that heavy exercise might be used to cause graded and well-defined amounts of muscle trauma, thereby serving as an experimental model for inflammation and sepsis. OBJECTIVE: In order to explore whether some form of strenuous exercise might provide an useful model for the inflammatory process, we studied the effects of three different exercise protocols on blood leukocyte count during and following exercise. DESIGN: Four different experimental conditions, using a randomized-block design. SETTING: Defence and Civil Institute of Environmental Medicine, North York, Ontario, Canada. PARTICIPANTS: Eight healthy and moderately fit males. PROCEDURES: Participants were each assigned to four experimental conditions. Subjects performed 5 minutes of cycle-ergometry exercise at 90%, 2 hours of cycle-ergometry exercise at 60%, a standard circuit of resistance exercises with 3 sets of 10 repetitions at 60 to 70% of one-repetition maximum (1- RM) force at each of 5 different stations; or they remained seated for 5 hours. DIAGNOSTIC TEST USED: Flow cytometric analysis. MAIN MEASUREMENTS: Blood samples were analyzed for total leukocyte counts, total T cells, T helper/inducer cells, T suppressor/cytotoxic cells, B cells, cytolytic T cells, and natural killer cells. RESULTS: The peak aerobic and prolonged submaximal exercise induced similar alterations in cell counts. These changes were generally larger than those produced by the resistance exercise, although both resistance and peak aerobic exercise resulted in a significantly longer-lasting decrease in the CD4+ / CD8+ ratio than the submaximal exercise bout did. CONCLUSION: The data suggest that, of the three exercise patterns tested, prolonged aerobic exercise induced the largest and most readily measured patterns of immune response. Nevertheless, the changes provided only a partial model for the clinical inflammatory process.